Non-Nutritive Suck Assessment Tool Development to Characterize Sucking Patterns in Infant with Various Hunger Levels - Saputra, Casmika; Inati, Iin (POSITRON, 2023)
Sucking abilities are critical in early infant development, and the patterns of non-nutritive suck (NNS) have been found to potentially predict neurodevelopmental issues in the future. Proper NNS assessments are essential to ensure valid conclusions. Previous studies have shown that the level of infant arousal significantly affects NNS patterns. However, the author did not find any studies that observed the influence of infant hunger levels on NNS patterns. Therefore, this study aimed to develop an NNS assessment tool to characterize NNS patterns in infants with various hunger levels. The NNS assessment was conducted using a pressure transducer connected to a pacifier. The results showed that the level of hunger significantly affected the intra-burst frequency and the sucking pressure. The more hungry the infant, the more frequent the intra-burst frequency became, while the sucking pressure tended to decrease. The intra-burst frequency of infant sucking was 2.3, 2.46, and 2.5 Hz on average for a relative hunger index of 0.67, 0.83, and 1.0, respectively. The NNS pressure of infant sucking was 6.31, 4.51, and 2.62 kPa on average for a relative hunger index of 0.67, 0.83, and 1.0, respectively. This study's results suggest that during NNS assessments, the measurement time should consider the next feeding schedule for the infant.